Polynomial Equations

1 / 14

# Polynomial Equations - PowerPoint PPT Presentation

Polynomial Equations. Whenever two polynomials are set equal to each other, the result is a polynomial equation. In this section we learn how to solve polynomial equations both graphically and algebraically by factoring. Solving Polynomial Equations Graphically. Example.

I am the owner, or an agent authorized to act on behalf of the owner, of the copyrighted work described.

## PowerPoint Slideshow about 'Polynomial Equations' - rollin

Download Policy: Content on the Website is provided to you AS IS for your information and personal use and may not be sold / licensed / shared on other websites without getting consent from its author.While downloading, if for some reason you are not able to download a presentation, the publisher may have deleted the file from their server.

- - - - - - - - - - - - - - - - - - - - - - - - - - E N D - - - - - - - - - - - - - - - - - - - - - - - - - -
Presentation Transcript
Polynomial Equations

Whenever two polynomials are set equal to each other, the result is a polynomial equation.

In this section we learn how to solve polynomial equations both graphically and algebraically by factoring.

Solving Polynomial Equations Graphically

Example

Find the zeros of the function given by f(x) = x3 – 2x2 – 5x + 6.

Solution

Graph the equation, choosing a window that shows the x-intercepts

of the graph. This may require several attempts.

To find the zeros use the ZERO option from the CALC menu.

continued f(x) = x3 – 2x2 – 5x + 6

Use the same procedure for the other two zeros.

Hence, the zeros/roots are x = -2, x = 1, and x = 3.

Example

Solution

(4, 0)

(3, 0)

Solving Polynomial Equations Algebraically

Example

Solve: (x – 4)(x + 3) = 0.

Solution

According to the principle of zero products, at least one factor must be 0.

x – 4 = 0 or x + 3 = 0

x = 4 or x = 3

For 4: For 3:

(x – 4)(x + 3) = 0 (x – 4)(x + 3) = 0

(4 – 4)(4 + 3) = 0 (3 – 4)(3 + 3) = 0

0(7) = 0 0(7) = 0

0 = 0 TRUE 0 = 0 TRUE

Terms with Common Factors (GCF)

When factoring a polynomial, we look for factors common to every term and then use the distributive law.

Multiply Factor

4x(x2 + 3x 4) 4x3 + 12x2  16x

= 4xx2 + 4x3x  4x4 = 4xx2 + 4x3x  4x4

= 4x3 + 12x2  16x = 4x(x2 + 3x 4)

Example

Factor: 28x6 + 32x3.

Solution

The prime factorization of 28x6 is

2  2  7  x  x  x  x  x  x

The prime factorization of 32x3 is

2  2  2  2  2  x  x  x

The greatest common factor is 2  2  x  x  x or 4x3.

28x6 + 32x3 = 4x3 7x3 + 4x3  8

= 4x3(7x3 + 8)

Example Factor: 12x5 21x4 + 24x3

Solution

The prime factorization of 12x5 is

2  2  3  x  x  x  x  x

The prime factorization of 21x4 is

3  7  x  x  x  x

The prime factorization of 24x3 is

2  2  2  3  x  x  x

The greatest common factor is 3  x  x  x or 3x3.

12x5 21x4 + 24x3 = 3x3 4x2  3x3  7x + 3x3  8

= 3x3(4x2 7x + 8)

Example

Solution

Factoring by Grouping

Example

Write an equivalent expression by factoring.

a) 3x3 + 9x2 + x + 3b) 9x4 + 6x 27x3  18

Solution

a) 3x3 + 9x2 + x + 3 = (3x3 + 9x2) + (x + 3)

= 3x2(x + 3) + 1(x + 3)

= (x + 3)(3x2 + 1)

Don’t forget to include the 1.

b) 9x4 + 6x 27x3  18

= (9x4 + 6x) + (27x3  18)

= 3x(3x3 + 2) + (9)(3x3 + 2)

= (3x3 + 2)(3x  9)

= (3x3 + 2)3(x  3)

= 3(3x3 + 2)(x  3)

Factoring and Equations

Example Solve: 7x2 = 35x.

Solution

Use the principle of zero products if there is a 0 on one side of the equation and the other side is in factored form.

7x2 = 35x

7x2 – 35x = 0 Subtracting 35x. One side is now 0.

7x(x – 5) = 0 Factoring

x = 0 or x – 5 = 0 Use the principle of zero products

x = 0 or x = 5

To Use the Principle of Zero Products

1. Write an equivalent equation with 0 on one side, using the addition principle.

2. Factor the polynomial completely.

3. Set each factor that is not a constant equal to 0.

4. Solve the resulting equations.

To Use the Principle of Zero Products

1. Write an equivalent equation with 0 on one side, using the addition principle.

2. Factor the polynomial completely.

3. Set each factor that is not a constant equal to 0.

4. Solve the resulting equations.